2016
DOI: 10.1111/bcpt.12538
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol Ameliorates Cisplatin‐Induced Nephrotoxicity in Rats

Abstract: Treatment with cisplatin is associated with dose-limiting side effects, mainly nephrotoxicity. On the other hand, nebivolol, a b 1 -adrenoceptor antagonist, exhibits vasodilatory and antioxidative properties. This study aimed to determine whether nebivolol possesses a protective effect against cisplatin nephrotoxicity and explore many mechanisms underlying this potential effect. Nephrotoxicity was induced in Wistar rats by a single intraperitoneal injection of cisplatin (6 mg/kg) on day 2. Nebivolol (10 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
6
29
0
Order By: Relevance
“…Co-treatment of rats with either Carv or Nebi showed a significant protective effect against the current Gly-induced RM-ARF model. This observed renoprotective effect is in agreement with the findings of studies that used Carv or Nebi as a protective agent against other models of ARF in which restoration of the normal levels of renal function biomarkers was reported [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Co-treatment of rats with either Carv or Nebi showed a significant protective effect against the current Gly-induced RM-ARF model. This observed renoprotective effect is in agreement with the findings of studies that used Carv or Nebi as a protective agent against other models of ARF in which restoration of the normal levels of renal function biomarkers was reported [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
“…The significant attenuation of Gly-induced oxidative stress in the rats treated with Carv or Nebi indicates that antioxidant pathway played a role in the renoprotective effects of both drugs. Many studies also reported this antioxidant effect of Carv and Nebi [ 49 , 51 ]. Carv has been found to scavenge oxygen radicals and inhibit their release from activated neutrophils [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 86%
“…In contrary, nebivolol markedly increased expression of eNOS which was weakly expressed with APAP hepatotoxicity. It was reported that nebivolol enhanced eNOS expression [25][26][27] and reduced iNOS expression [28]. Induction of iNOS expression was associated with hepatotoxicity of other models, and its reduction was linked to hepatoprotective effect [29][30][31].…”
Section: Scoring Of Hepatic Enos Expression C O N T R O L a P A P A Pmentioning
confidence: 99%
“…The most frequent diabetes-related complications are cardiovascular diseases and atherosclerosis, and the main troublesome complications in the elderly are heart and kidney insufficiencies (Chentli et al, 2015). These complications could exacerbate chemotherapy-induced toxicity and worsen cancer symptoms (Psarakis, 2006;Malik et al, 2016;Morsy & Heeba, 2016;).…”
Section: The Role Of Diabetes-related Complications Severitymentioning
confidence: 99%
“…Although the severity of diabetes complications could contribute to higher mortality among women with diabetes, little is known about the impact of severity of diabetes-related complications on risk of all-cause mortality among incident BC cases. Evidence from previous literature has revealed that the presence of some diabetes complications could affect cancer therapy (Morsy & Heeba, 2016;Peairs et al, 2011;, which could impact patients' health outcomes. However, there are limited evidence in the literature on the direct impact of overall severity of diabetes-related complications on all-cause mortality of incident BC after controlling for cancer therapy and other possible risk factors.…”
Section: Introductionmentioning
confidence: 99%